Jejunogastric retrograde intussusception: case report and literature review - Bermúdez, Jorge; Barreneche, Omar (Cirugía del Uruguay, 1972)
A case of retrograde jejunogastric intussusception successfully reduced by operation, is presented and analized by the authors. The literature on the subject is reviewed and the authors expose diagnostical, pronostical and terapeuthical conclusions.